The Personal Finance Behavioral: Digital Finance, Financial Knowledge And Financial Attitudes (Study on Mercu Buana University Students) - Saputri, Ayu Laynda; Risman, Asep (Universitas Mercu Buana, 2025)
Digitalization has become the factor to sustainable economic growth, every country including Indonesia continues to encourage digitalization in all sectors. The development of technology whose function is for transactions from various economic activities carried out by Mercu Buana University students, this study aims to analyze the influence of digital finace, financial knowledge, and financial attitudes towards financial behavior in Mercu Buana University students. To obtain data in this study by distributing questionnaires to students with a total of 100 respondents, with data analysis carried out using Partial Least Square (PLS) software. This research proves that funds show that digital finance has a positive effect on student financial behavior. And financial knowledge positively influences financial behavior and financial attitudes positively also influence financial behavior.